Pengaruh Kesulitan Membaca terhadap Kepercayaan Diri Anak Usia 6–12 Tahun dalam Berkomunikasi: Studi di Desa Lau Dendang, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang - Adam Elvano Tambunan; Dedek Fadilla Tri Julianta Tarigan; Nurul Afifah; Estefanie Lamtiur Gultom; Nazwa Alya Fasya; Sany Klara Nainggolan; Zaskia Aisyah; Grace Zippora Sembiring; Lina Margaret; Fauzi Kurniawan; Anifah Pilliang (STKIP Subang, 2026)
This qualitative descriptive study examines how reading difficulties influence self‑confidence in classroom communication among children aged 6–12 in Desa Lau Dendang. Using purposive sampling (n = 12), data were collected through classroom observation, semi‑structured interviews with students and teachers, and documentation of reading activities. Thematic analysis identified three main themes: reduced oral participation, reading anxiety manifesting as avoidance behaviors, and the mitigating role of teacher and parental support. Practical recommendations include targeted remedial reading, structured speaking opportunities, and family‑school collaboration to strengthen both literacy and communicative confidence.